Optical analysis of Müller glia cells as light transporters through the retina - Szabó, Levente; Erdei, Gábor; Maák, Pál Andor (Biomedical optics express, 2022)
One and half decades ago, Müller glia cells of the retina became subjects of extended research as optical waveguides. It was demonstrated that outside the fovea, these cells are capable of providing light transmission through the thicker parts of the retina from the vitreous surface to the photoreceptor cells. We combined optical modeling of the eye’s optical system with numerical methods that describe light guiding within Müller cells to analyze efficiency of light capture and guidance at different peripheral positions. We show that higher order guided modes play an important role, especially in the case of higher incidence angles and extended geometry of the electromagnetic field distributions predicted by the eye’s optical model. We analyze the mode structure excited at different retinal peripheral positions and show that actual construction of these cells optimizes light guiding. Our results refine previously published modeling results regarding Müller cells as waveguides and provide extension to the whole area of the retina.